Prevalence of vertebral fractures in women and men in the population-based Tromsø Study - Waterloo Svanhild (BMC Musculoskeletal Disorders, 2012)
Abstract Background Osteoporotic vertebral fractures are, as the hip fractures, associated with increased morbidity and mortality. Norway has one of the highest reported incidences of hip fractures in the world. Because of methodological challenges, vertebral fractures are not extensively studied. The aim of this population based study was to describe, for the first time, the age- and sex specific occurrence of osteoporotic vertebral fractures in Norway. Methods Data was collected in the Tromso Study, 2007/8 survey. By the use of dual x-ray absorptiometry (GE Lunar Prodigy) vertebral fracture assessments were performed in 2887 women and men aged from 38 to 87 years, in addition to measurements of bone mineral density at the femoral sites. Information on lifestyle was collected through questionnaires. Comparisons between fractures and non-fractures were done sex stratified, by univariate analyses, adjusting for age when relevant. Results The prevalence of vertebral fractures varied from about 3% in the age group below 60 to about 19% in the 70+ group in women, and from 7.5% to about 20% in men, with an overall prevalence of 11.8% in women and 13.8% in men (p = 0.07). Among those with fractures, only one fracture was the most common; two and more fractures were present in approximately 30% of the cases. Fractures were seen from the fourth lumbar to the fifth thoracic vertebrae, most common between first lumbar and sixth thoracic vertebrae. The most common type of fracture was the wedge type in both sexes. Bone mineral density at the hip differed significantly according to type of fracture, being highest in those with wedge fractures and lowest in those with compression fractures. Conclusions The prevalence of vertebral fractures increased by age in women and men, but the overall prevalence was lower than expected, considering the high prevalence of hip and forearm fractures in Norway. In both sexes, the wedge type was the fracture type most frequently observed and most common in the thoracic region.